Jenis Makanan dan Area Makan Ikan Tongkol Abu-abu (Thunnus tonggol) yang didaratkan di PPI Kedonganan pada Musim Barat - Putu Niken Ayu Saraswati; Pande Gde Sasmita Julyantoro; Gde Raka Angga Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2020)
Kedonganan Fish Landing Port is part of Bali Strait which is one of longtail tuna habitat. There was no study about biological parameters on longtail tuna in Bali Strait especially in Kedonganan fish landing port. This study aims to determine fullness gastric contents of the longtail tuna landed at the Kedonganan Fish Landing Port and find out the composition and type of food contained in the stomach of the longtail tuna. This research was carried out for 5 months from October 2018 to January 2019. Analysis data used included percentage of 1 type of food, frequency of occurrence and index of gastric fullness. The results showed that the type of food found in the longtail tuna gut were small fish, squid and dissolved food. The frequency of occurrence of small fish has a percentage 80.5%, which means small fish is the main food of longtail tuna. The highest gastric fullness index was in November 2018 which showed that in November 2018 longtail tuna was actively looking for food. Longtail tuna is actively looking for food, but the eating activities decreased which is suspected at that time the availability of food decreased because of southwest monsoon. The food that contained in the longtail tuna gut were small fish, squid and dissolved food. Longtail tuna is a carnivorous fish because its main food was small fish and can be classified as stenophagic. Longtail tuna usually looking for food in the area around Uluwatu, Nusa Dua and Takacamung